La homonimia y sus implicaciones legales en Colombia (2019)
This work is based on an analysis of Homonymy in Colombia, the consequences and implications that a person may have for having a name similar or equal to another. A detailed study is done on the Homonymy case with the aim of providing in a clear and precise manner based on current Colombian law and regulations. The work is developed with some objectives which are to analyze, identify the legal framework and indicate the different implications and finally determine the responsibility and consequences of Homonymy in the Colombian state. This degree work is carried out by the real case happened to the author of this legal study (Jose Antonio Lopez Barbosa) who, due to his identification data as a citizen and the same name of a person with a criminal record for drug trafficking, collateral damage occurs in against his good name that affected him not only personally and socially, but also legally. With this investigation of Homonymy and its legal implications in Colombia, a contribution is made to the legal vacuum that the current regulations have in place and a proposal is made in comparative law where foreign laws are already regulating this type of phenomenon.